Animals of Nusantara: Virtual Reality-Based English Learning Materials for Secondary Students - Made Hery Santosa; I Dewa Ayu Ogik Vira Juspita Banjar (Nusantara Science and Technology Proceedings, 2024)
Virtual Reality (VR) has come to a point for more authentic learning as it provides opportunities for learners to visit various places or objects they cannot physically see and do because of school and home boundaries. A preliminary observation and interview were conducted to disclose the teachers’ views on the use of the previously released Animals of Nusantara (AoN) VR application implemented in public and private schools in North Bali, Indonesia. They admitted to be somewhat familiar with the application after several trial attempts. Despite the positive learning supports, the teachers also faced problems in implementing this authentic learning media in the English instruction in the metaverse era. This situation led to the development of VR for English Learning handbook to fulfill teachers’ queries on adequate information about authentic media, tutorials on using AoN VR application, and meaningful learning activity ideas. ADDIE model was employed as the research design. Instruments used include an interview guide, a checklist, and expert judgments’ evaluation sheet. All gathered data were analyzed qualitatively and quantitatively. It was found that this handbook is as excellent media to assist teachers in teaching English in secondary school level, meaning that the book can be one potential learning resource for English instruction in the metaverse era. It is suggested that the teachers to utilize this handbook to implement authentic learning in the class projects while delving into interesting information provided by the VR application.